Government expenditure and economic growth in the EU : long-run tendencies and short term adjustment - Arpaia, Alfonso; Turrini, Alessandro 1966-; European Commission : Directorate-General for Economic and Financial Affairs (Brussels- Belgium : European Comission : Directorate-General for Economic and Financial Affairs, 2008)
This paper analyses both the long and the short-run relation between government expenditure and potential output in EU countries by means of pooled mean group estimation (Pesaran, Shin, and Smith (1999)). Results show that, over a sample comprising EU-15 countries over the 1970-2003 period, it cannot be rejected the hypothesis of a common long-term elasticity between cyclically-adjusted primary expenditure and potential output close to unity. However, the long-run elasticity decreased considerably over the decades and is significantly higher than unity in catching-up countries, in fast-ageing countries, in low-debt countries, and in countries with weak numerical rules for the control of government spending. The average speed of adjustment of government expenditure to its long-tem relation is 3 years, but there are significant differences across countries. Anglo-Saxon and Nordic countries exhibit in general a faster adjustment process, while adjustment in Southern European countries appears somehow slower.
Economic Papers.